ФУНКЦИОНАЛЬНОЕ СОДЕРЖАНИЕ ПРОЦЕССА УПРАВЛЕНИЯ ПРОИЗВОДИТЕЛЬНОСТЬЮ КАК ОДНОЙ ИЗ ПОДСИСТЕМ МЕНЕДЖМЕНТА ПРЕДПРИЯТИЯ - Карибаев, Е.С.; Казбеков, Т.Б. (Изд-во КарГУ, 2010)
Өнімді жобалау жəне өндіру үшін қолданылатын ресурстардың жоғары өнімділігіне қол жеткізу тəсілін шешудің айрықша маңыздылығы көрсетілген. Əрбір ірі еуропалық елде өнімділіктің өңірлік жəне салалық орталықтары желісін құру тəжірибесі жалпыланған. Кəсіпорын менеджментінің кіші жүйесі ретіндегі еңбек өнімділігін басқару үдерісінің функционалды мазмұны, еңбек өнімділігін арттыру бағдарламасын тиімді жүзеге асыру шарттары келтірілген. The special meaningfulness of decision of problem of achievement of high yield of resources, in-use for development and issue of products is underlined. Experience of networking regional and of a particular branch centers of the productivity is summarized in every large European country. Functional maintenance of process of management the productivity opens up as to one of subsystems of management of enterprise. The necessity of development of strategy and programs of growth of the labour productivity is grounded on domestic enterprises. The terms of effective realization of the programs of growth of the labour productivity are selected.